Двозначність інтертексту: джерела й функції цитацій у романі Павла Загребельного «Я, Богдан (Сповідь у славі)». Стаття перша - Назаренко, М. (Слово і Час, 2022)
У статті на прикладі численних алюзій прозаїка до творів світового письменства продемонстровано, що однозначність ідеологічного змісту роману істотно ускладнюється завдяки введенню в текст прямих і прихованих цитат з авторів, що жили вже після Хмельниччини: розповідач цитує як українських (Митрофан Довгалевський, Григорій Сковорода, Тарас Шевченко, Олекса Стороженко, Михайло Коцюбинський, Володимир Сосюра та ін.), так і зарубіжних письменників (Вільям Фолкнер, Анна Ахматова, Борис Пастернак). Анахронічні цитати формують образ гетьмана як утілення всієї української історії та культури у світовому контексті, а прихований інтертекстуальний діалог підважує цілком офіціозні тези, висловлені експліцитно. The paper is the first part of a study on the poetics of intertext in Pavlo Zahrebelnyi’s novel “I, Bohdan”. The work by Zahrebelnyi vividly illustrates the difference between the intention of the author and the intention of the text. The writer’s self-commentaries were inevitably ideologically engaged, while the intention of the text, that is, the textual strategy of the novel, can be reconstructed. Special attention should be paid to the textual points where the senses are generated and tensions or contradictions between diff erent levels of the text emerge — especially those between direct utterance and intertextual subtext. Thus, the definition of the intention of the text is at the same time its deconstruction, in the Derridian sense of the word. The unambiguity of the ideological content of the novel is greatly complicated by the introduction of the direct and hidden quotations and allusions to the writers who lived and worked long aft er Khmelnytskyi’s time. These authors may be Ukrainian (Skovoroda, Shevchenko, Franko, Kotsiubynskyi, Tychyna, Sosiura), Russian (Pushkin, Akhmatova, Pasternak, Bakhtin), European and American (Mickiewicz, Faulkner, Churchill). The narrator of the novel is Bohdan Khmelnytskyi, a monument in the Kyiv square and at the same time a hetman who’s dying in 1657. The hero exists beyond time and at every point in time. Anachronistic quotations contribute to the creation of the image of the hetman as the embodiment of all the Ukrainian history and culture in the world context. The narrator sometimes enters into a dialogue with the authors of the original texts and may argue with them. Numerous (or even all) literary versions of Khmelnytskyi’s image, in the Polish and Ukrainian paradigms, the late populist and the socialist realist ones, are presented as dubious or simply false. The main objects of controversy are Sienkiewicz (as the author of the novel most hostile to the hetman) and Shevchenko (as the author most critical towards Khmelnytskyi in the Ukrainian tradition). Bohdan as the founder of the new Ukrainian nation is equal to Shevchenko as a historical figure and prophet; the narrator of the novel, although he disagrees with Shevchenko’s opinion, still cites it. The reader, in the end, must decide for himself whom he trusts more and for what reason. Since Shevchenko’s ruthless words are quoted in the first chapter of the novel, the rest should be read in this — extremely ambiguous — ideological perspective.